EFFECTIVE USE OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN THE EDUCATIONAL SYSTEM (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this article, the author talks about the effective use of ICT in the education system, as well as the ongoing reforms in our country in this field. The author analyzes the situation and shares his views on the subject.